The Impact of External and Internal Factors on Strategic Management of Innovation Processes at Company Level - Shatilo, Oksana (Ekonomika, 2020)
The impact of external and internal factors on organization of operation at company level is studied. The necessity for implementing strategic management of innovation processes at company level is substantiated. The structural interactions of external and internal factors on the organization of company operation are determined; a classification of factors of external and internal environment in the context of strategic management of innovation processes at company level is constructed.
Keywords: external environment; internal environment; strategic management; innovation processes; companies